The subjective experiences of divorced men in the South African context - Meirim, Hugo Miguel Neves (My University, 2009)
ABSTRACT This research project focused on the subjective experiences of divorce, experienced by men within the South African context. It involved conducting focus groups, as well as individual interviews, with the aim of eliciting common themes. The data was analysed using thematic content analysis and the themes were then categorized with the assistance of Bronfenbrenner’s ecological theory of development. This provided a framework to order the myriad themes that emerged through the interviews, which varied from emotional responses to the prolonged and complex stressor sequence that is divorce, legal issues around custody, as well as the broader financial and social impact experienced by the men involved. These themes included the negative as well as positive impacts experienced by divorced men.